1971
DOI: 10.1073/pnas.68.12.2994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures of DNA-Dependent RNA Polymerases (II) from Calf Thymus and Rat Liver

Abstract: DNA-dependent RNA polymerase II has been purified to high specific activity and apparent homogeneity from both calf thymus and rat liver. Two form II enzymes are present in rat-liver preparations, one with the molecular structure 1(190,000)i(150,000),(35,000)1(25,000)dl, the other with a molecular structureof [(170,000),(150,000) -(35,000),(25,000),] (molecular weights are within ±5% but the absolute values are approximate). Inclusion of a proteolytic inhibitor during the isolation procedure decreases the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

1972
1972
1989
1989

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 14 publications
4
37
1
Order By: Relevance
“…Clearly, there is no evidence of any increase in the number of RNA polymerase molecules synthesising RNA in the presence of heparin as would be the case if blocked transcription complexes were being released. The value for the number of form B molecules measured in this study is in agreement with that published by Weaver et al [33] who estimated, from the specific activity of purified rat liver enzyme and the a-amanitin-sensitive activity in crude extracts, that 10000 molecules were present per nucleus. This value reduces to about 6500 molecules per diploid genome when corrected for the presence of tetraploid nuclei [22].…”
Section: Number Of Transcribing R N a Polymerase Moleculessupporting
confidence: 82%
“…Clearly, there is no evidence of any increase in the number of RNA polymerase molecules synthesising RNA in the presence of heparin as would be the case if blocked transcription complexes were being released. The value for the number of form B molecules measured in this study is in agreement with that published by Weaver et al [33] who estimated, from the specific activity of purified rat liver enzyme and the a-amanitin-sensitive activity in crude extracts, that 10000 molecules were present per nucleus. This value reduces to about 6500 molecules per diploid genome when corrected for the presence of tetraploid nuclei [22].…”
Section: Number Of Transcribing R N a Polymerase Moleculessupporting
confidence: 82%
“…Comparison of the efficiency of our method with those reported by Stein and Hausen [9] and by Weaver et at. [17] for the solubilization and separation of the amanitinsensitive activity is impossible, since these authors did not state the yield of activity per weight of thymus. Applied to rat liver nuclei [15], our method was also more efficient in solubilizing the amanitinsensitive activity than those reported by other groups [18,19].…”
Section: Characteristics Of a And B Activitiesmentioning
confidence: 99%
“…Weaver et al (10) have suggested that RNA polymerase II of calf thymus is composed of four polypeptide chains of molecular weights 190,000, 150,000, 35,000, and 25,000. Kedinger et al (11,12) were clarified by high-speed centrifugation as described (5).…”
mentioning
confidence: 99%